Pengaruh Rotasi Kerja Terhadap Kinerja Pegawai Kantor Bea Cukai Kediri Melalui Work Life Balance - Adi, Bagus Novy; Talkah, Abu (Otonomi, 2025)
This study aims to analyze the effect of job rotation on employee performance with work-life balance as a mediating variable at the Kediri Customs Office. Using a quantitative approach with a survey method, data were collected from 83 active employees through a closed questionnaire. Data analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0. The results show that job rotation has a positive effect on work-life balance and directly improves employee performance. Work-life balance also positively influences performance and mediates the effect of job rotation on performance. These findings suggest that structured and planned job rotation can enhance employee skills, reduce burnout, and support a healthier work environment, ultimately boosting organizational performance..